Time use and values of time and reliability in the Netherlands - Gerard de Jong; Marco Kouwenhoven (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper compares the survey results of three value of travel time (VTT) surveys conducted in the Netherlands since the late 1980s. It discusses the method used in the Dutch studies for estimating VTT for business travel; the importance of travel time reliability; and the impacts of distance and productive or pleasant use of travel time on VTT. By comparing how VTT has evolved over time, this paper discusses potential impacts of technological changes on VTT and the use of VTT in project appraisals in the future.
Keywords: 330